2022
DOI: 10.17503/agrivita.v44i2.2539
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Heavy Rainfall and Wind Velocity During Flowering Affect Rice Production

Abstract: Journal of Agricultural Sciencewww.agrivita.ub.ac.id 290 in the absence of irrigation facilities, the rice-growing period absolutely depends on the availability of rainfall.Recently, securing food crop production including rice is a great challenge due to the escalation of the intensiy and frequency of extreme weather incidents as the impacts of global climate change (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…The majority of very high levels of risk are in the maintenance stage, both the vegetative and the generative phase (growth, flowering and fertilization). Wind and rain during flowering can reduce rice production [12] the generative phase has the highest total RPN according to reference [13] The generative phase of rice is more susceptible to rain than the vegetative phase. The recommended recommendation in managing this risk is to transfer risk.…”
Section: Financial Risk Identificationmentioning
confidence: 99%
“…The majority of very high levels of risk are in the maintenance stage, both the vegetative and the generative phase (growth, flowering and fertilization). Wind and rain during flowering can reduce rice production [12] the generative phase has the highest total RPN according to reference [13] The generative phase of rice is more susceptible to rain than the vegetative phase. The recommended recommendation in managing this risk is to transfer risk.…”
Section: Financial Risk Identificationmentioning
confidence: 99%
“…The lack of a relationship between typhoon wind speed and rice is possibly due to the stronger cyclones missing the vulnerable growing and harvesting periods for rice. Rice plants were the most vulnerable to wind speeds of between 8 and 70 km/h at the heading stage and 14-30 days after heading [5], and it was possible that most typhoons may have occurred when the rice plants were less prone to wind damage.…”
Section: Rice Damage Not Solely Due To Strong Windsmentioning
confidence: 99%
“…Crops like bananas, pomelos, and papayas are vulnerable to strong winds as fruits and branches are easily blown off, while the roots and leaves of melon crops and leafy vegetables are easily damaged by flooding and storm surges [4]. The growth stage of the plant is also another critical factor that may affect the extent of crop damage [4][5][6]. Rice plants at the heading stage are particularly prone to lodging induced by excessive wind and the weight of water on the canopy from the rain associated with a typhoon.…”
Section: Introductionmentioning
confidence: 99%
“…This value is an indication of a strong relationship between rainfall and rice production, or, alternatively, a decrease in rice production as a result of an increase in rainfall. A study by [32] showed that high precipitation affected panicle filling and increased the number of unfilled grains. Although rainfall is beneficial in terms of increase in water availability, excessive amount of rainfall will be an abiotic stress on rice plants.…”
Section: Impact Of Changes In Rainfall On Rice Production In West Jav...mentioning
confidence: 99%
“…With a correlation value of 0.75, the results of the Pearson correlation analysis show that the vulnerability ratio has a significant impact on production. Based on the Seemingly Unrelated Regression (SUR) analysis conducted by [32], it was found that West Java Province was the area most affected by climate change. This result also supports a recent study conducted by [38], which found that agricultural intensification through mechanisation is a strategy to mitigate climate change, although it is still implemented by few farmers.…”
Section: Level Of Vulnerability To Climate Change Impactsmentioning
confidence: 99%